Calibration of Measurement Tools in the Experimental Test Rig for Hydropower Performance Evaluation - Mdee, Ombeni J.; Kimambo, Cuthbert Z.; Nielsen, Torbjorn K.; Kihedu, Joseph (Tanzania Journal of Engineering and Technology, 2025)
The demonstration of a typical hydropower plant requires thedevelopment of a test rig with the installation of tools to measure theperformance parameters. The measurement tools require a calibrationprocess to improve the quality of recorded data. This study involved thecalibration of traditional and automated measurement tools connectedto the hydropower test rig through an Arduino microprocessor. Theautomated measurement tools included a pressure transducer, flowmeter, digital tachometer, and torque transducer, while traditionalmeasurement tools, including a pressure gauge, concrete water tank,contact tachometer, and force lever arm balance, were connected intheARTICLE INFOSubmitted: Apr. 23,2024Revised: Nov. 26, 2024Accepted: Jan, 30,2025Published: June, 2025same test rig during the calibration process. Arduinomicroprocessor was employed with code to generate signals whenconnected to automated measurement tools. The results of automatedtools varied linearly with traditional measurement tools, with Rsquared closer to 1. Therefore, this study recommended thatcalibrating automated measurement tools during experimental testingis essential for accurately assessing the performance of the test rigdevelopment